Photosynthetic oxygen-self-generated 3D-printing microbial scaffold enhances osteosarcoma elimination and prompts bone regeneration - He, Chao; Dong, Caihong; Hu, Hui; Yu, Luodan; Chen, Yu; Hao, Yongqiang (Nano today, 2021)
•Photosynthetic oxygen-self-generated 3D-printing microbial scaffold achieves enhanced photodynamic therapy.•Oxygen-self-generated 3D-printing microbial scaffold exerts favorable osteogenic capability in vitro and in vivo.•mRNA transcriptome deciphers the potential biological mechanism to throw light on further optimization.•The bionic 3D-printing microbial scaffold realizes the practical demands of efficient OS elimination and bone regeneration. A multifunctional oxygen-self-generated therapeutic platform has been developed by integrating the photosensitive and photosynthetic Ce6-contained cyanobacteria onto 3D-printing CaCO3-PCL scaffolds for the enhanced photodynamic therapy (PDT) against OS and the subsequent prompted bone regeneration, which has been systematically demonstrated both in vitro and in vivo. Especially, mRNA sequencing was employed to further decipher the underlying therapeutic mechanisms. [Display omitted] Osteosarcoma (OS) is the most frequent bone tumor which mainly threatens children and adolescents. The current mainstream therapeutic strategies for OS are surgical resection, chemotherapy and radiotherapy. However, the critical bone defects after the surgical resection, chemotherapy resistance and adverse effects are still formidable obstacles in the OS treatment. Herein, a multifunctional and exquisite photosynthetic oxygen-self-generated therapeutic platform has been engineered by integrating the photosensitive and photosynthetic Ce6-contained cyanobacteria onto 3D-printing CaCO3-PCL scaffolds, which has achieved the enhanced photodynamic therapy (PDT) against OS by photosynthetic oxygenation-induced tumor-hypoxia alleviation and the subsequent prompted bone regeneration by local oxygenation. Especially, mRNA sequencing (RNA-seq) was employed to further decipher the underlying mechanisms, which indicated that cell proliferation was inhibited and cell death was induced responding to the reactive oxygen species (especially the singlet oxygen) related cytotoxicity. This study provides an insightful design and efficient paradigm for the bacteria-enhanced PDT against OS and the following augmented osseous tissue regeneration.